Collaborative Post-Mining Area Management in Kampoeng Reklamasi Air Jangkang, Bangka Regency, Indonesia - Indi Agung Pratama; Oekan S. Abdoellah; Budhi Gunawan (Institut Pemerintahan Dalam Negeri, 2023)
Abstract The mining sector is one of the significant contributors to revenue structure of the country but despite evident material benefits, certain problems often occur. One example is found in Tin mining, where aside from creating pits, reclaimed post-mining areas still retain the potential for community cultivation due to residual tin deposits. To address these concerns, efforts have been made to engage various stakeholders through the collaborative management method in the post-mining area. Currently, this method is being implemented in Kampoeng Reklamasi Air Jangkang, Merawang District. Therefore, this study aimed to measure the achievements of collaborative post-mining area management implemented at Kampoeng Reklamasi Air Jangkang. The mixed methods were used with a concurrent design measured through three variables, namely Economic, Social, and Ecological. The results showed that collaborative post-mining area management fell into the